2018
DOI: 10.3390/w10020124
|View full text |Cite
|
Sign up to set email alerts
|

A Wall Boundary Condition for the Simulation of a Turbulent Non-Newtonian Domestic Slurry in Pipes

Abstract: Abstract:The concentration (using a lesser amount of water) of domestic slurry promotes resource recovery (nutrients and biomass) while saving water. This article is aimed at developing numerical methods to support engineering processes such as the design and implementation of sewerage for concentrated domestic slurry. The current industrial standard for computational fluid dynamics-based analyses of turbulent flows is Reynolds-averaged Navier-Stokes (RANS) modelling. This is assisted by the wall function appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 33 publications
1
27
0
Order By: Relevance
“…These experiments are then used to develop a suitable simulation methodology to enable industrial studies and applications such as the design of a waste water system carrying concentrated domestic slurry. This article is in line with Mehta et al [4] that outlines a modification to the Newtonian wall function proposed by Launder and Spalding [5], to enable the simulation of the wall-bounded turbulent flow of a Herschel-Bulkley fluid. This modification (mentioned in Mehta et al [4] as ψ 1 or ψ 2 ) was shown to improve the accuracy in terms of estimating frictional losses in a pipe carrying a turbulent Herschel-Bulkley fluid.…”
supporting
confidence: 79%
See 4 more Smart Citations
“…These experiments are then used to develop a suitable simulation methodology to enable industrial studies and applications such as the design of a waste water system carrying concentrated domestic slurry. This article is in line with Mehta et al [4] that outlines a modification to the Newtonian wall function proposed by Launder and Spalding [5], to enable the simulation of the wall-bounded turbulent flow of a Herschel-Bulkley fluid. This modification (mentioned in Mehta et al [4] as ψ 1 or ψ 2 ) was shown to improve the accuracy in terms of estimating frictional losses in a pipe carrying a turbulent Herschel-Bulkley fluid.…”
supporting
confidence: 79%
“…Following the idea put forth by Launder and Spalding [5], a relation between the wall shear stress and the velocity near a wall for a Herschel-Bulkley fluid was derived in [4] based on Prandtl's theory [18,19]. Readers are also referred to the book by Skelland [8] that presents the derivation of the original Newtonian law of the wall.…”
Section: A Wall Function For a Non-newtonian Fluidmentioning
confidence: 99%
See 3 more Smart Citations